Establishing Pattern Sequences Using Stochastic Trees and Bayesian Belief Networks With an Application to Security Patterns - Viktor Matovic; Valentino Vranic (IEEE Access, 2025)
Organizational patterns can be applied to correct problems or build a new organization from scratch. Security patterns can help organizations develop secure software. Security in organization can be established using sequences of organizational and security patterns. Security patterns can help organizations develop secure software. Although isolated applications of one or more security patterns are typical in practice, an effective response to security threats requires the utilization of an entire pattern catalog. Composing software patterns in a particular sequence order makes them more efficient. Solutions for establishing sequences of security and organizational patterns are often documented in plain text using explicit pattern relationships. Identifying the most probably used security and organizational patterns from their text descriptions allows us to establish meaningful sequences from these patterns. In this work, we show how we established 14 sequences of security patterns using the strongest symmetries of the relationships. We calculated the strongest symmetries of relationships between patterns identified in the Bayesian belief network as conditionally dependent patterns. We calculated the strongest symmetries of relationships using conditional probabilities of security pattern use with the stochastic tree built on deliberately chosen sequences of security patterns. Sequences of security patterns established in this way can be used after meaningful sequences of organizational patterns to implement security in the working organization. The applicability of belief networks and stochastic trees is not limited to security or organizational patterns. We consider applying them to patterns engineering software for cloud.